Frequency and Total Harmonic Distortion Estimation Based on Adaptive Filters - Moya, Sergio Eduardo (2013)
In this paper, a low computacional cost total harmonic distortion and frecuency estimation method is proposed. This method is based on adaptive digital filters allowing tracking the fundamental frequency variations. Real time experimental results obtained using a fixed point digital signal processor development kit are presented. They show an acceptable performance and have a robust behavior to signal distortions such as frequency fluctuations, high harmonic content, subharmonic and interharmonics.